Incomplete sensorimotor paresis after upper abdominal surgery with TEA and spinal epidural lipomatosis: a case report - Zugaj, Marco; Gutzeit, Oliver; Mayer, Victoria Louise; Ishak, Basem; Gumbinger, Christoph; Weigand, Markus A.; Keßler, Jens (Regional anesthesia and pain medicine, 2024)
Introduction This case report documents a postoperative, incomplete sensorimotor paraparesis from thoracic vertebral body 6 (Th6) after combined anesthesia for upper abdominal surgery in a patient who had a thoracic localization of spinal epidural lipomatosis (SEL). - Case presentation The patient was treated in our clinic with a thoracic epidural catheter (TEA) for perioperative analgesia during a partial duodenopancreatectomy. Paraparetic symptoms occurred 20 hours after surgery. Initial MRI did not show bleeding, infection or spinal cord damage and the neurosurgeon consultants recommended observation. The neurological examination and the third follow-up MRI on 15th postoperative day showed ventrolateral damage of the spinal cord at level Th6. It is possible that local anesthetic compressed the spinal cord in addition to the existing lipomatosis and the thoracic kyphosis. The paraparesis improved during follow-up paraplegiologic treatment. - Conclusion So far, only two uncomplicated lumbar epidural catheter anesthesias have been described in patients who had a lumbar SEL. Epidural catheter anesthesia is a safe and effective method of pain control. But it is important to carefully identify and stratify patients with risk factors during the premedication visit. In patients who had kyphosis and thoracic localization of SEL, TEA may only be used after a risk-benefit assessment.
Gesehen am 24.07.2024